Could the arm blood pressure measured with simultaneous bilateral arm method be used for hypertension diagnosis? - Taixuan Wan; Yuanhao Wu; Ziqiang He; Hai Su (BMJ Open)
Objective Simultaneous bilateral arm blood pressure (BP) measurement (bilateral arm method) is suggested for the first BP measurement in clinical practice, but whether the arm BP measured with bilateral arm method (RA-2) is similar to that with unilateral arm method (RA-1) is unclear.Design Quantitative research, paired sample T-test, Bland-Altman and multivariate linear regression analyses were used.Setting This study included 295 subjects (18–90 years, 60.0±14.6 years old, 126 males) in the clinic of cardiovascular medicine of the Second Affiliated Hospital of Nanchang University. They were randomly instructed to one of two BP measurement proposals: (1) right-arm–bilateral arm–right-arm–bilateral arm, or (2) bilateral arm–right-arm–bilateral arm–right-arm to attenuate bias induced by BP measurement order.Participants From June to October of 2019, 295 outpatients (18–90 years, 60.0±14.6 years old, 126 males and 169 females) with sinus rhythm (SR) were enrolled. The exclusion criteria were acute myocardial infarction, congenital heart disease, acute heart failure, syncope, hemiplegia, arrhythmia and pulseless (by palpation).Outcome measures We compared the BP differences between bilateral arm method and unilateral arm method. The difference between RA-2 and RA-1 was calculated as Dif-RA. Data are expressed as means±SD for continuous variables. The percentage increase (PI) was calculated on the formula: (RA-2−RA-1)/RA-1.Results The RA-2 on systolic blood pressure (SBP)/diastolic blood pressure (DBP) was slightly, but statistically higher by 1.2/0.4 mm Hg against the RA-1. Multivariate regression analyses showed that hypertension therapy type was positive impact factor, but RA-1 was negative factor for PI of Dif-RA on SBP, DBP and pulse pressure.Conclusion The SBP and DBP of right arm measured with bilateral arm method are slightly, but statistically higher (1.2 and 0.4 mm Hg) than those with the unilateral arm BP method.